Age Differences in Visual Attention and Responses to Intergenerational and Non-intergenerational Workplace Conflicts - Yeung, Dannii Y.; Isaacowitz, Derek M.; Lam, Winnie W. Y.; Ye, Jiawen; Leung, Cyrus L. K. (Frontiers in Psychology, 2021)
Intergenerational conflict occurs commonly in the workplace because of age-related differences in work attitudes and values. This study aimed to advance the current literature on aging and work by examining whether younger and older workers differ in their visual attention, emotional responses, and conflict strategies when observing hypothetical conflict vignettes involving a coworker from a similar or dissimilar age group. The indirect effect of age group on emotional responses and conflict strategies through visual fixation on conflict scenes was also examined. Utilizing eye tracking, the visual attention of younger and older workers while watching two hypothetical workplace task conflict videos was recorded and compared. The participants were also asked to imagine how they would respond if they were the main actor in the vignettes. A total of 94 working adults, including 48 younger workers and 46 older workers, participated in the eye tracking experiment. Older workers reported fewer negative and more positive emotions than their younger counterparts after watching the conflict videos, particularly those on the non-intergenerational conflict. Younger workers used more dominating in the intergenerational conflict than in the non-intergenerational conflict; such discrepancy between conflict types was relatively small in older workers. Compared with younger workers, older workers fixated significantly less on the coworker during the intergenerational conflict scenes. A significant indirect effect of age group through visual fixation on the coworker was observed for positive emotions and avoiding. Results revealed that older workers may regulate their emotional reactions and conflict strategies to workplace conflicts by reducing their attention to negative stimuli.